Analysis of Internal and External Factors of L'amore Coffee Shop - Wiradisuria, Ranendra Kreshnatama; Syamsiyah, Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The trend of coffee shops in Bandung as a place to socialize and work is increasing with many new cafes appearing and a large amount of coffee consumption. This study aims to analyze the internal and external environmental conditions of L'amore Coffee. The research method used is descriptive qualitative with a case study approach. Data was collected through interviews, observations, and documentation, then analyzed using the IFE (Internal Factor Evaluation) matrix, and EFE (External Factor Evaluation). The results of the IFE analysis show that L'amore Coffee has two main strengths such as its strategic location for commercial activities and the organization of various collaborative events. Meanwhile, L'amore Coffee's two weaknesses are L'amore Coffee's lack of information disseminated through various media and stakeholders and there are wobbly or less sturdy chairs and tables. The results of the EFE matrix analysis show that there are two main opportunities that can be utilized, including the lifestyle and culture of people who never stop consuming coffee and the trend of coffee shops always increasing as a place to culinary, work, and gather. Meanwhile, the two biggest threats that can occur at L'amore Coffee are if the conduciveness of L'amore Coffee cannot be controlled so that it can disturb local residents and coffee shop competitors that are increasingly emerging.